4(2a1)2(2a-1)^{2} -36(a3)2(a-3)^{2}

asked by guest
on Jan 29, 2025 at 12:07 pm



You asked:

Evaluate the expression: 4(2a1)236(a3)24 {\left( 2 a - 1 \right)}^{2} - 36 {\left( a - 3 \right)}^{2}

MathBot Answer:

Evaluated



4(2a1)236(a3)2=4(2a1)236(a3)2\displaystyle 4 {\left( 2 a - 1 \right)}^{2} - 36 {\left( a - 3 \right)}^{2} = 4 \left(2 a - 1\right)^{2} - 36 \left(a - 3\right)^{2}


Expanded

4(2a1)236(a3)2=20a2+200a3204 {\left( 2 a - 1 \right)}^{2} - 36 {\left( a - 3 \right)}^{2} = - 20 a^{2} + 200 a - 320


Factored

4(2a1)236(a3)2=20(a8)(a2)4 {\left( 2 a - 1 \right)}^{2} - 36 {\left( a - 3 \right)}^{2} = - 20 \left(a - 8\right) \left(a - 2\right)